CHART FILLING AS A TRANSFER INFORMATION ACTIVITY IN TEACHING LISTENING COMPREHENSION AT SMAN 1 BENTENG, SELAYAR - Anwar, Tri Yuliana; Naro, Wahyuddin; YT, St. Nurjannah (ETERNAL (English, Teaching, Learning, and Research Journal), 2017)
This thesis is aimed to find out the improvement of students’ listening comprehension at the third grade of SMAN 1 Benteng Selayar in using Chart filling method. The researcher applied quasi-experimental design with non-equivalent controlled group design. The population of this research was the third grade of SMAN 1 Benteng, which consisted of 296 students. The research subject was the first semester students of III IPA 1 and III IPA 2. The researcher chose 40 students as a sample of the research with 20 students as experimental class and 20 students as control class that selected by using purposive sampling technique.There were two research variables: Independent variable and Dependent variable. The independent variable of this research was Chart filling method. On the other hand, students’ listening comprehension was dependent variable. The result of the data analysis indicated that there was a significant improvement in the students’ listening comprehension after being taught using Chart filling method as a listening method. It was proved by the result of the statistical analysis of the level significance P = 0.05 with degree of freedom (df)=38 indicated that the t-test values of the students’ listening comprehension (5.28) was greater than t-table (2.086). Based on the finding and discussion of the research, the researcher suggested that Chart filling was able use in teaching students’ listening comprehension. And the researcher concluded that Chart filling method was effective to improve students’ listening comprehension at the third grade of SMAN 1 Benteng, Selayar.